Empowering University Students: Advancing Human Rights Knowledge and Advocacy Through Human Rights Defender Schools - Pratiwi, Cekli Setya; Sunaryo, Sidik (Indonesian Journal of Legal Community Engagement, 2025)
Human rights violations, including violence, intolerance, and discrimination, persist within university communities, underscoring the need for systematic education to foster awareness and advocacy. To empower students to prevent and advocate human right violations, lecturers of Universitas Muhammadiyah Malang (UMM) launched the Human Rights Friendly Campus (HRFC) program in 2024/2025, supported by the Internal Community Service Program (PPMI) and partnerships with key stakeholders, including the Center for the Study of Civilization and Human Rights and the Indonesian Consortium of Human Rights Lecturers (SEPAHAM Indonesia).  Central to this initiative is the Human Rights Defender School, designed to provide students with philosophical, legal, and practical knowledge of human rights and advocacy. Utilizing adult learning methodologies and a student-centered learning (SCL) framework, the program actively engaged 40 student activists, focusing on participatory education through discussions, debates, advocacy skills trainings and tutorials as well as field trip. The program achieved significant outcomes, including improved participant understanding of human rights, the development of a tailored curriculum for student activists, and the formation of an ad-hoc Human Rights Defender Community under UMM’s Student Executive Body. These results highlight the program’s success in bridging knowledge gaps and fostering a culture of advocacy within the campus. This initiative demonstrates the potential for higher education institutions to integrate human rights education into their academic frameworks, promoting inclusive and respectful campus environments. With its replicable model, the HRFC program provides a strategic approach to cultivating human rights awareness and advocacy, positioning universities as pivotal actors in advancing human rights values.